Development of adaptive experiential learning via interactive contemporary education with extended reality (A) - Pong, Stella Ke Xin (2019)
In today’s day and age of technology, one expects learning and teaching pedagogies to be diversified and tailored to various learners. However, it is evident that despite efforts to move away from the teacher-centred traditional classrooms, the needs of learners with learning disabilities such as autism and dyslexia have not been addressed. Teachers struggle to track a learner’s progress and check if the learning objectives are met. As per Paul Kirschner [1], technologies are tools to enable a student’s learning only if appropriately used; it is effective only if there is a reciprocal relationship between the interactive lesson and its students whereby learners should not just obtain resources from the environment without contributing additional information to it. While there is an initiative in movement for utilising other mediums (besides the conventional pen and paper) e.g. ICT, eBook platforms for learning, these mediums have not been appropriately used to their fullest potential, which this project (AELVICE) seeks to delve into with the exploration of Extended Reality (XR), with the focus on Virtual Reality (VR) and the potential of incorporating machine learning. The main features of AELVICE includes volume level, eye-contact, and pronunciation accuracy.